Colorectal adenocarcinoma cancer in New Zealand in those under 25 years of age (1997–2007). Issue 5 (16th September 2013) - Plunkett, Michael; Murray, Melissa; Frizelle, Frank; Teague, Lochie; Hinder, Victoria; Findlay, Michael
Abstract Introduction Colorectal cancer is common and primarily a disease of older people. Colorectal cancer in patients aged 25 years and under is infrequent and may represent a unique subgroup of patients. This study aimed to describe the population of young people in New Zealand diagnosed with colorectal cancer, their tumour characteristics, management and outcomes. Methods A retrospective clinical study was conducted via review of medical records for all patients 25 years of age and under, diagnosed with colorectal adenocarcinoma in New Zealand between 1 January 1997 and 31 December 2007. Results Fifty patients with colorectal adenocarcinoma were identified from the New Zealand Cancer Registry. Seven had a positive family history of colorectal cancer, while eight had predisposing factors (hereditary nonpolyposis colorectal cancer, familial adenomatous polyposis, ulcerative colitis, Crohn's disease, regional enteritis). The most common presenting symptoms were abdominal pain and weight loss. Twenty‐eight cases presented acutely. Eighteen presented with stage IV disease at diagnosis. Eighteen were referred to a genetics service. Five‐year overall survival was 49%. Discussion Those aged 25 years and under that develop colorectal cancer tend to present acutely and move through the secondary care pathway swiftly, being diagnosed at a more advanced stage, and have a poorer prognosis than their adult counterparts. Familial cancers form a more significant component of youth colorectal cancers compared to the older population and input from genetic service should be considered.